Answer:
f=14 or f=34
Step-by-step explanation:
(x+d)(x+e) =x^2 +fx+33, d, e, f>0
x^2 +xe+dx+de=x^2+fx+33
x^2+(e+d)x+de=x^2 +fx+33 that
e+d=f and d*e=33, d=33/e
e+33/e=f
33=1*33 or 33=3*11
If e=1,d=33 then f=34
If e=3*,d=11, then f=14
Answer:
Y=-2x
When x= -6 then y =12
Step-by-step explanation:
If y and x in direct variation then y=c*x for some constant c.
We are told
-4=c2
——> c= -2
So y= -2x
When x= -6 this becomes
Y= (-2) * (-6)
——> y = 12
Answer:
7.5 miles
Step-by-step explanation:
2.5 times 3
hope this can help you :-P
The answer would be 2.5.
hope this helps (;
Answer:
I think the answer is 24 minutes!
Step-by-step explanation:
I hope this helps!